Membingkai Kedermawanan di Era Digital: Analisis Wacana Akun Instagram Semangat Sedekah : Framing Generosity in the Digital Era: A Discourse Analysis of the Instagram Account Semangat Sedekah - Romario, Romario (Universitas Darussalam Gontor, 2025)
The internet has influenced religious expression, both in terms of patterns, attitudes, and responses. Almsgiving as a practice of piety in Islam to give wealth to those in greater need, has shifted. Almsgiving, which was initially managed by the Musola and Mosque in the neighborhood, is now being managed by a number of philanthropic communities that use the internet. Especially after the presence of social media, this philanthropic community has found it easier to attract donors, promote the motives for almsgiving, the targets of people who are given alms, and the rewards of good deeds for those who give alms. This study focuses on one of the almsgiving communities on social media, namely Semangat Sedekah. Using a netnographic approach, this study analyzes how Semangat Sedekah displays the discourse of almsgiving, promotes almsgiving, and donor responses to Semangat Sedekah. This study shows that Semangat Sedekah attracts social media followers by linking to the Berbagi Semangat account which posts viral and humorous videos, then on the Semangat Sedekah account after displaying a number of posts about children who are seriously ill and orphans. The transparency carried out by Semangat Sedekah has been able to build trust for Semangat Sedekah donors through websites and videos that show that Alms have been given to those in need.